2020
DOI: 10.1557/jmr.2020.48
|View full text |Cite
|
Sign up to set email alerts
|

Defect-induced optical and electrochemical properties of Pr2Sn2O7 nanoparticles enhanced by Bi3+ doping

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Blue emission in CSO can also be clearly seen from the CIE index diagram shown as Figure S2 of SI. Based on an earlier report on inorganic oxides, such visible emission is attributed to the presence of defects in the band gap of materials, viz., cation vacancies, anion vacancies, interstitials, etc. ,, Such blue emission has been previously observed in 1D chain-type structures such as Sr 2 CeO 4 and Ca 2 Sn 1– x Ce x O 4 wherein authors have attributed the same to oxygen-to-metal charge transfer. , Blue emission could also be observed in other hosts such as CaZrO 3 , SrTiO 3 , Nd 2 Zr 2 O 7 , Zn 2 P 2 O 7 , Pr 2 Sn 2 O 7 , SrZrO 3 , Sr 2 SnO 4 , MgAl 2 O 4 , etc. ,,, wherein the origin of such emission is attributed to OVs. In the literature, we could find only two reports wherein authors have carried out emission spectroscopy of CSO. , Both the groups have contradictory remarks about this emission; Yu et al have attributed the same simply to OVs, whereas Gao et al have ascribed the same to O 2– → Sn 4+ ligand-to-metal charge transfer, and in fact, they have pointed out that OVs quench the blue emission in CSO.…”
Section: Resultssupporting
confidence: 54%
“…Blue emission in CSO can also be clearly seen from the CIE index diagram shown as Figure S2 of SI. Based on an earlier report on inorganic oxides, such visible emission is attributed to the presence of defects in the band gap of materials, viz., cation vacancies, anion vacancies, interstitials, etc. ,, Such blue emission has been previously observed in 1D chain-type structures such as Sr 2 CeO 4 and Ca 2 Sn 1– x Ce x O 4 wherein authors have attributed the same to oxygen-to-metal charge transfer. , Blue emission could also be observed in other hosts such as CaZrO 3 , SrTiO 3 , Nd 2 Zr 2 O 7 , Zn 2 P 2 O 7 , Pr 2 Sn 2 O 7 , SrZrO 3 , Sr 2 SnO 4 , MgAl 2 O 4 , etc. ,,, wherein the origin of such emission is attributed to OVs. In the literature, we could find only two reports wherein authors have carried out emission spectroscopy of CSO. , Both the groups have contradictory remarks about this emission; Yu et al have attributed the same simply to OVs, whereas Gao et al have ascribed the same to O 2– → Sn 4+ ligand-to-metal charge transfer, and in fact, they have pointed out that OVs quench the blue emission in CSO.…”
Section: Resultssupporting
confidence: 54%
“…For example, Abraham et al explained the electrochemical properties of PSO based on doping heterogeneous compounds (defect chemistry) . In PSO, Pr 3+ (8-coordination of the ideal cube structure) shows the large ionic size (Pr ion: 112.6 pm) and small moment, followed by interaction with Sn 4+ (6-coordinated distorted octahedral coordination), which will lead to the creation of more electronic charges, thereby improving the electron transfer path for the electrochemical reactions . Based on these concepts, we believe that the Pr 2 Sn 2 O 7 pyrochlore oxide is a suitable candidate for electrochemical sensing of target molecules.…”
Section: Introductionmentioning
confidence: 97%
“…Based on this aspect, a few types of rare-earth or lanthanide stannates (LSO) such as La 2 Sn 2 O 7 , Dy 2 Sn 2 O 7 , and Nd 2 Sn 2 O 7 are widely used as an electrocatalyst for various applications including photocatalysis, electrochemical conversion, and storage because of their significant properties in terms of high surface area, fast charge transferability, high melting point, lower activation energy, eminent chemical stability, and ionic mobility. It is observed that there is a strong conflict between the accelerated covalent interactions in the continuous filling of 4f orbital which results in the enhancement of ionicity and higher electronegativity among rare-earth oxides (RE-O). Among these lanthanide stannate series, praseodymium stannate (Pr 2 Sn 2 O 7 -PSO) is a highly trending material in electrochemical studies, due to their unique crystal structure and high spin–orbital coupling interaction . In addition to that, this coupling effect relates to the strong quantum confinement (phonon interaction) accompanied by a change in heterogeneous spin-state, and may lead to the occurrence of unbalanced Coulombic charge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research on metal oxide nanoparticles (NPs) in the field of photocatalysis is an area of intensive interest and the use of metal oxides as photocatalysts is attracting more and more interest by the day. 23–28 Basically, the mechanism of photocatalysts depends on electron–hole pair formation upon irradiation, 29 whereas there are some drawbacks that hinder the practical applications of photocatalysts, such as the quick recombination of charge carriers and the low utilization of light during the photocatalytic process. Hence, to achieve good quantum efficiency in photocatalysis, the electron–hole pair separation efficiency and the ability of light utilization of the photocatalysts should be enhanced.…”
Section: Introductionmentioning
confidence: 99%